Hemodynamic Instability after Low-Energy Thigh Contusion Caused by Injury to the Femoral Artery: A Case Report and Literature Review - Juan Miguel Rodríguez-Roiz; José Ballesteros-Betancourt; Raquel García-Tarriño; Victor Antonio Rodríguez-Roiz; Manuel Llusa (Case Reports in Orthopedics)
Acute vascular injuries have been described in relation to high-energy trauma accidents or in patients undergoing surgery in the femoral area. We describe a healthy patient who sustained a direct, low-energy contusion in the thigh and presented haemodynamic instability. Arteriography was used to locate the point of bleeding, and embolisation and vessel occlusion were carried out to stop the haemorrhage. The genetic study identified the COL3A1 gene mutation; accordingly, the patient was diagnosed with the Ehlers-Danlos syndrome type IV (vascular type).